2018
DOI: 10.12930/nacada-17-039
|View full text |Cite
|
Sign up to set email alerts
|

Event History Analysis for Investigating the Likelihood and Timing of Changing Majors

Abstract: Students change their majors for various reasons, and academic advisors often assume the role of facilitating that change through institutional agreements or contracts. Therefore, advisors need to identify time periods during enrollment with the greatest likelihood that students will seek to change majors. They must also examine the student characteristics associated with changing majors so that advisors can identify students to avoid delays to graduation. The relationship between student characteristics and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Globally, university students are typically allowed to change their major subjects (or even change university) due to multifarious reasons (e.g., insufficient prior knowledge during subject selection, being homesick, not finding the subject as interesting as they thought, not coping with course demands after admittance). [29][30][31]65 American studies claim that approximately 46%-80% of students change their major subjects once they enroll in universities. 30,65 However, in Bangladeshi universities, there is very limited scope to rotate or change the major subjects or university.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, university students are typically allowed to change their major subjects (or even change university) due to multifarious reasons (e.g., insufficient prior knowledge during subject selection, being homesick, not finding the subject as interesting as they thought, not coping with course demands after admittance). [29][30][31]65 American studies claim that approximately 46%-80% of students change their major subjects once they enroll in universities. 30,65 However, in Bangladeshi universities, there is very limited scope to rotate or change the major subjects or university.…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31]65 American studies claim that approximately 46%-80% of students change their major subjects once they enroll in universities. 30,65 However, in Bangladeshi universities, there is very limited scope to rotate or change the major subjects or university. Therefore, students who find their current academic subjects or institutions uninteresting may be unable to cope after the initial stage of their study (i.e., during their 1st year of study).…”
Section: Resultsmentioning
confidence: 99%
“…Within the Social Sciences, Humanities, and Education proportions of men and women are similar (Patnaik et al, 2020). Sklar (2018) investigated the likelihood of changing majors based on gender, ethnicity, and pre-college preparation. Results showed that women had a greater risk of changing majors than men when initially enrolled in Engineering or Architectural Design colleges at the university/study site.…”
Section: Demographic Factors Major Changes and Completionmentioning
confidence: 99%
“…Inadequate advising and support for students to enroll in relevant, credit-bearing courses early in their academic journey can lead to increased time to graduation or dropping out altogether (Foraker, 2012;Kadlec & Dadgar, 2020;Kramer et al, 1994;Moore & Shulock, 2009). It is also less understood how demographic and background characteristics relate to how and when students change majors (Sklar, 2018;Wang & Orr, 2022). Therefore, in this study, we sought to determine if there was a relationship between changing majors and degree attainment and if changes of academic majors impact students differentially based on their background characteristics.…”
mentioning
confidence: 99%
“…A central goal of these departments and programs is to ensure students identify an academic path that fits their interests, uses their skills, and aligns with their values by the time they complete the first college year. The emphasis on first-year exploration avoids the potential consequences of multiple major changes, such as delayed graduation and extra financial costs (Denice, 2021;Sklar, 2018). This paper explores data from two cohorts enrolled in an FYS course designed to cater to the needs of exploratory students.…”
mentioning
confidence: 99%